Patients with myeloproliferative neoplasms and COVID‐19 have increased rates of arterial thrombosis. Issue 5 (11th August 2022) - Leiva, Orly; Campia, Umberto; Snyder, Julia; Barns, Briana M.; Rizzo, Samantha; Khairani, Candrika D.; Brunner, Andrew; Al‐Samkari, Hanny; Leaf, Rebecca Karp; Rosovsky, Rachel; Goodarzi, Katayoon; Bornikova, Larissa; et al.
Abstract: Background: Both coronavirus disease‐2019 (COVID‐19) and myeloproliferative neoplasms (MPNs) are associated with systemic inflammation and risk of thrombosis. Risk of thrombosis in patients with COVID with and without MPNs has not been extensively studied. Methods: Retrospective cohort study of 44 patients with MPNs and 1114 patients without MPNs positive for SARS‐COV‐2. Outcomes were arterial thrombosis (AT), venous thromboembolism (VTE), bleeding, and death. Time‐to‐event analysis was performed using competing risk regression model and Cox proportional hazards. Results: AT occurred more frequently in patients with MPN (7% vs. 1%, p  = 0.03). Rates of VTE (7% vs. 5%, p  = 0.73), bleeding (7% vs. 2%, p  = 0.06), and death (9% vs. 6%, p  = 0.32) were similar. MPN patients were older and had more cardiovascular comorbidities. After time‐to‐event competing‐risk regression adjusting for age, MPN patients had higher risk of AT (subdivision hazards ratio 3.95, 95% CI 1.09–14.39) but not VTE, bleeding, or death. Conclusions: Among patients with COVID‐19, MPN patients had higher risk of arterial thrombosis but not VTE, bleeding, and death compared with non‐MPN patients. Larger studies are needed to confirm our findings given the limited sample size.